Respiratory health of brickworkers in Cape Town, South Africa. Radiographic abnormalities. - Myers, J. E.; Garisch, D.; Louw, S. J. (Scandinavian Journal of Work, Environment & Health, 1989)
A cross-sectional study utilizing internal controls based on dust exposure determinations was performed on 268 brickworkers. Smoking, age, and other information from a detailed respiratory questionnaire and results from a physical examination and pulmonary function tests were investigated in relation to radiographic abnormality. The prevalence of pneumoconiosis was near 4%. The roles of smoking, workplace dust exposure, and age as factors predicting radiographic abnormality are discussed.